2021
DOI: 10.3390/rs13224617
|View full text |Cite|
|
Sign up to set email alerts
|

In Situ Determination of Dry and Wet Snow Permittivity: Improving Equations for Low Frequency Radar Applications

Abstract: Extensive efforts have been made to observe the accumulation and melting of seasonal snow. However, making accurate observations of snow water equivalent (SWE) at global scales is challenging. Active radar systems show promise, provided the dielectric properties of the snowpack are accurately constrained. The dielectric constant (k) determines the velocity of a radar wave through snow, which is a critical component of time-of-flight radar techniques such as ground penetrating radar and interferometric syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The lower elevations showed no accumulation in the InSAR retrievals, and this was confirmed by both the HQ met snow depth sensors and snow pit (Figure 8b). These results illustrate the ability to Corresponding research by Webb et al (2021b) investigated the relationship between dielectric permittivity and LWC for both dry and wet snow conditions in the Jemez Mountains. With ρ s ranging between 261 to 309 kg m −3 and ϵ s between 1.26 to 1.39, snowpack LWC would range approximately between 3% to 5%.…”
Section: ∆Fsca Vs Insar ∆Swesupporting
confidence: 60%
See 1 more Smart Citation
“…The lower elevations showed no accumulation in the InSAR retrievals, and this was confirmed by both the HQ met snow depth sensors and snow pit (Figure 8b). These results illustrate the ability to Corresponding research by Webb et al (2021b) investigated the relationship between dielectric permittivity and LWC for both dry and wet snow conditions in the Jemez Mountains. With ρ s ranging between 261 to 309 kg m −3 and ϵ s between 1.26 to 1.39, snowpack LWC would range approximately between 3% to 5%.…”
Section: ∆Fsca Vs Insar ∆Swesupporting
confidence: 60%
“…This validates figures presented in Leinss et al (2015), which state that at L-band (1.26 Ghz), and a ρ s of 300 kg m −3 , the radar signal can penetrate between about 10 m at 1% LWC and 1 m at 10% LWC. The high quality of the phase signal even with relatively high LWC shows promise for the overall performance of NISAR and it's 6 AM and 6 AM sun-synchronous orbit even when snowpacks contain some LWC (Webb et al, 2021b). By processing the 12-26 February pair, we've shown that coherence can be held and quality snow phase information can be obtained at a 14 day temporal baseline, even in the presence of melt.…”
Section: ∆Fsca Vs Insar ∆Swementioning
confidence: 94%
“…We observed a good correlation between probe and GPR measurements (Figures 3a and 3b), and the calibrated snow radar velocity (0.189 ± 0.023 m ns −1 ) has an uncertainty of ∼12%. However, our calibrated velocity is slower than observed in previous works, typically between 0.23 and 0.25 m ns −1 (e.g., Bradford, Harper, & Brown, 2009; McGrath et al., 2022); and it is also slower than expected for a snow density of 360 kg m −3 using empirical relationships that correlates dry snow density and radar velocity (e.g., Kovacs et al., 1995; Tiuri et al., 1984; Webb et al., 2021). This discrepancy may be attributed to differences in snow properties at the Arctic lowland compared to, for example, alpine mountains.…”
Section: Discussionmentioning
confidence: 90%
“…GPR has been widely applied in snow investigations across different regions, including alpine mountains (e.g., Bradford, Harper, & Brown, 2009; McGrath et al., 2022), Arctic Coastal Plain of Alaska (e.g., Wainwright et al., 2017), Greenland (e.g., Gacitúa et al., 2013; Jaedicke & Sandvik, 2002), boreal regions (e.g., Gusmeroli & Grosse, 2012), and Antarctic sea ice (e.g., Pfaffhuber et al., 2017). The snow radar velocity can be calibrated based on direct snow depth probe measurements; the radar velocity in dry snow is fundamentally controlled by the snow density (Tiuri et al., 1984; Webb et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We categorized surveys as dry or wet based on the presence of any LWC noted in snow pits and corroborated by pit temperatures (Appendix A.2; Figure S2). Relative permittivity estimates obtained in dry‐snow conditions (all surveys, except the 7 April and 27 May 2021 surveys) were then converted to density using the Kovacs et al (1995), Kuroiwa (1954), and Webb et al (2021) equations and compared to in‐situ density measurements to calculate the RMSE and Pearson correlation coefficient to determine the most representative equation.…”
Section: Methodsmentioning
confidence: 99%